2022
DOI: 10.30773/pi.2021.0230
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Smartphone and Internet Gaming Addiction on Eating Attitudes Among University Students

Abstract: Objective Smartphone addiction is a public health problem increasing with the technologic developments. It particularly affects the university students negatively in terms of psychological, physical, academic achievement and social relations. This study aims to investigate the relation of eating attitudes between smartphone addiction and internet gaming disorder, also the relation of smartphone addiction with obesity.Methods This cross-sectional and prospective study is consisted of 358 volunteer university st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The prevalence of gaming disorder among young adults is reported to be 10-15% in Asia and 1-10% in the Western countries [28]. Additionally, studies evaluating the health status of adolescents and young adults during the COVID-19 pandemic reported that internet addiction and gaming disorders exert an adverse effect on health, causing disorders, such as obesity and weight gain, due to sleep deficit [29][30][31]. Moreover, in Japan, with the spread of COVID-19 infection, the incidence of internet gaming disorder has increased [32], and the association with weight gain may have been confirmed as one of the phenotypes of this health disorder in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of gaming disorder among young adults is reported to be 10-15% in Asia and 1-10% in the Western countries [28]. Additionally, studies evaluating the health status of adolescents and young adults during the COVID-19 pandemic reported that internet addiction and gaming disorders exert an adverse effect on health, causing disorders, such as obesity and weight gain, due to sleep deficit [29][30][31]. Moreover, in Japan, with the spread of COVID-19 infection, the incidence of internet gaming disorder has increased [32], and the association with weight gain may have been confirmed as one of the phenotypes of this health disorder in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it has been suggested that sleep disturbance disrupts the circadian rhythm and is associated with obesity and hepatic and intestinal diseases caused by the dysregulation of the physiological functions of hepatocytes, gastrointestinal cells, and adipocytes [22,23]. In studies that evaluated the health status of adolescents and youth in the COVID-19 pandemic, game usage and gaming disorder as well as smartphone addiction were reported to exert an adverse effect on health leading to disorders, such as overweight and weight gain via sleep deficit [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Other research also demonstrated an association between a higher degree of IGD and a higher prevalence of inadequate dietary habits [45]. The attempt to prolong game periods can lead to the choice of more convenient but less nutritionally adequate food options, such as fast food, and longer periods of distraction can decrease the awareness of what is being ingested and decrease the ability to regulate food ingestion [50]. It is also likely that increasing professionalization, implying a higher commitment to esports, results in less concern with following a healthy eating pattern.…”
Section: Mediterranian Diet Adherencementioning
confidence: 99%